2020
DOI: 10.1200/po.20.00097
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-1 Can Lead to Immune Evasion in Metastatic Castration-Resistant Prostate Cancer

Abstract: PURPOSE Metastatic castration-resistant prostate cancer (mCRPC) with low androgen receptor (AR) and without neuroendocrine signaling, termed double-negative prostate cancer (DNPC), is increasingly prevalent in patients treated with AR signaling inhibitors and is in need of new biomarkers and therapeutic targets. METHODS Candidate genes enriched in DNPC were determined using differential gene expression analysis of discovery and validation cohorts of mCRPC biopsies. Laboratory studies were carried out in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 36 publications
(55 reference statements)
2
38
0
1
Order By: Relevance
“…Sui et al reported that DKK 1 impairs the tumor response to PD-1 blockade by inactivating CD8 + T cells in colorectal cancer [14]. Another study demonstrated that metastatic castration-resistant prostate cancer (mCRPC) tumors with high DKK1 expression exhibit a CD8 + T-cell-poor tumor microenvironment in ltrated with immature M0 macrophages and M2 macrophages [31]. Our analysis and the results of these study have a mutual veri cation effect.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Sui et al reported that DKK 1 impairs the tumor response to PD-1 blockade by inactivating CD8 + T cells in colorectal cancer [14]. Another study demonstrated that metastatic castration-resistant prostate cancer (mCRPC) tumors with high DKK1 expression exhibit a CD8 + T-cell-poor tumor microenvironment in ltrated with immature M0 macrophages and M2 macrophages [31]. Our analysis and the results of these study have a mutual veri cation effect.…”
Section: Discussionsupporting
confidence: 61%
“…Zhang et al [39] demonstrated that MT1-deletion can be an independent prognostic factor in hepatocellular carcinoma. David et al found that DNA methylation as a likely mechanism that governs DKK1 expression in metastatic castration-resistant prostate cancer [31]. A further implication of this result is that elevated DKK1 could be a resistance mechanism to therapeutic DNA methyltransferase inhibition, which is currently being tested in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a phase II trial combining pembrolizumab with the CXCR1/CXCR2 antagonist navarixin in mCRPC patients is currently ongoing (NCT03473925). Additionally, Wise and colleagues described Dickkopf-1 (DKK1) gene expression as a novel contributor to the immunosuppressive TME of mCRPCs with low AR and without neuroendocrine signaling [ 118 ]. These data provided the rationale for an ongoing clinical trial targeting DKK1 in mCRPC (NCT03837353).…”
Section: Mechanisms Of Resistance and Potential Predictive Biomarkers Of Ici Responsementioning
confidence: 99%
“…17 DKN-01 (Leap Therapeutics, Cambridge, Mass., USA) is a humanized IgG4 monoclonal antibody that binds and neutralizes circulating DKK1 and has demonstrated nonclinical singleagent activity in DKK1-expressing tumor models. 18 Combination work with anti-PD-1 agents suggested enhanced activity in murine models. 17 We conducted a phase Ib trial exploring the safety and preliminary clinical activity of DKN-01 alone or in combination regimens in previously treated, advanced EGC patients.…”
Section: Introductionmentioning
confidence: 99%